2016
DOI: 10.3390/cli4040059
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Climate Adaptation Cultures in Global Context: Proposal for an Explanatory Framework

Abstract: This paper aims at enhancing the previously formulated culture-theoretical explanation of risk-related perception and action with ecological and institutional connectedness. This is needed for global comparison of adaptation cultures as well as transferability of local knowledge. Differences in climate-related patterns of knowledge will therefore be explained by common patterns of socially shared knowledge in relation to ecological and institutional transformation. This will be done by combining a cultural-kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(9 citation statements)
references
References 46 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…The climate resilience evaluation on agricultural system can be examined for other perturbations and expanded to other regions in the MLR. Recent study has shown that understanding of local culture is important to assess the climate change adaptation [61]. In future study, we need to consider the cultural knowledge on adaptation and investigate how it influences on agricultural systems in the MLR under climate change.…”
Section: Discussionmentioning
confidence: 99%
“…The climate resilience evaluation on agricultural system can be examined for other perturbations and expanded to other regions in the MLR. Recent study has shown that understanding of local culture is important to assess the climate change adaptation [61]. In future study, we need to consider the cultural knowledge on adaptation and investigate how it influences on agricultural systems in the MLR under climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Chowdhury et al (2011) reported that, due to worse overall socio-economic situation along the Naaf River, the children in fishing communities were co-opted in fishery related activities rather than engaging in education. Besides, the literature shows that local environmental knowledge plays a vital role in adapting response strategies to the climatic events (Heimann and Mallick 2016;Adger et al 2013;Price et al 2014) and therefore, it is assumed under this study that there will be significant diversity in responses to the climatic events and hazards taken by the migratory and non-migratory fishers.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The Padma River is also affected by the climatic hazards and disasters (Vineis et al 2011;Mohsin et al 2013) and therefore, this study on the Padma River fishery dependent migratory and non-migratory communities has an importance for national level policy implication. Besides, the literature shows that local environmental knowledge plays a vital role in adapting response strategies to the climatic events (Heimann and Mallick 2016;Adger et al 2013, Price et al 2014 and therefore, it is assumed under this study that there will be significant diversity in responses to the climatic events and hazards taken by the migratory and non-migratory fishers. Accordingly, a conceptual 'difference triangle' and analytical model is proposed (Figure 1).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Climate change Bskepticism^refers to the act of rejecting, disputing, or questioning scientific evidence that the global climate is changing, that human actions are responsible for these changes, and that without mitigation and adaptation, serious consequences for humankind may result van Rensburg 2015). Literature on perceptions of climate change in developed countries broadly indicates that value orientations, beliefs, identities as well as scientific uncertainty influence mitigation and adaptation practices Heimann and Mallick 2016). More specific evidence with regards to climate change skepticism suggests that continued public disbelief regarding the trends, causes, and consequences of climate change exerts a strong influence on mitigation and adaptation behavior Engels et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although widely studied in developed nations Engels et al 2013), climate change skepticism has not been previously investigated among rural people in lowincome countries (Heimann and Mallick 2016). Skepticism in a low-income country context may result from many influences including low education, lack of access to information, and perhaps most importantly, from increased prevalence of religious and fatalistic beliefs (Schmuck 2000).…”
Section: Introductionmentioning
confidence: 99%